EVALUATION OF THE ECONOMIC POTENTIAL OF GOLD DEPOSITS BY THE ANALYSIS OF OXIDIZED ORE OUTCROPS AND EXOGENIC AUREOLS: METHODS USE IN THE U.S.S.R - Roslyakov N.A.; Roslyakov N.V. (My University, 1986)
In the majority of cases, new auriferous deposits, including some which are unique, are being discovered in regions with, at the most, only a thin allochthonous (transported) cover and this trend is likely to continue. Such deposits occur close to the present day surface, but because of the effects of atmospheric agents, they may be intensively transformed by hypergene processes. In general, it is very difficult to estimate the composition of the primary ores and to predict the depth at which they occur by study of oxidized ore outcrops and the geochemical anomalies from released elements which occur in the overlying soils. This paper considers the major geological-geochemical features of oxidized outcrops and hypergene halos which develop over the principal types of ore deposits. Particular attention is paid to the different geological and climatic conditions which form the basis by which the principles of estimating the composition of, and depth to, the original ores may be determined. The method is based on the analysis of the hypergene transformation products.